Transformation of the Social Insurance Management Agency on Health (Medico Legal Update, 2021)
Health insurance is a type of insurance product that specifically guarantees the cost of health or care ofthe insurance members if they are sick or have an accident. Implementation of social security is a stateobligation mandated by the 1945 Constitution. The issuance of the Social Insurance Management Agency(BPJS) act as the implementer of the National Social Security System act (SJSN) resulted in PT Askestransforming into Social Insurance Management Agency on Health (BPJS Kesehatan). The National SocialSecurity System is organized on the basis of humanitarian principles, principles of benefit, and the principleof social justice for all Indonesians. The National Social Security System aims to provide and guaranteesthe fulfillment of a decent life base for each participant and/or his family member. The National SocialSecurity System is organized on the basis of such principles: mutual cooperation, non-profit, disclosure,prudence, accountability, portability, mandatory membership, trust fund, and the social security fund willbe used entirely for program development and for the interest of participants. Although the preparation andimplementation of the National Social Security System is quite well, but in reality there are still variousimpacts and problems encountered in the operation of BPJS Kesehatan such as lack of socialization, servicefacilities, inappropriate data, and personnel who are still lacking in giving a good services and information.